(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Respiratory distress is a leading cause of neonatal morbidity and mortality, particularly in preterm infants. Bubble continuous positive airway pressure (bCPAP) has emerged as an effective non-invasive respiratory support modality. This study aimed to evaluate the clinical profile and outcomes of neonates with respiratory distress managed with bCPAP. Methods: A prospective observational study was conducted over 12 months (April 2023-April 2024) at a tertiary care neonatal unit. Neonates with respiratory distress (Downes/Silverman-Anderson score 4-6) were included. Demographic data, clinical parameters, duration of CPAP support, and outcomes were analyzed. Statistical analysis was performed using chi-square and Fisher’s exact tests. Results: Of 165 neonates enrolled, 68.5% were preterm. The most common etiology was respiratory distress syndrome (RDS, 61.8%), followed by transient tachypnea of newborn (TTN, 17.0%). Overall success rate of bCPAP was 77.0%. CPAP failure requiring mechanical ventilation occurred in 23.0%, with 17.6% mortality. Gestational age significantly influenced outcomes, with <28 weeks showing 100% failure rate (p<0.001). Complete antenatal steroid coverage improved outcomes in preterm neonates (77.8% recovery vs 47.6% in non-recipients, p=0.02). Higher Downes/SA scores (≥6), PEEP ≥6 cm H₂O, and FiO₂ >60% predicted CPAP failure. Pneumothorax was associated with 75% mortality. Conclusion: Bubble CPAP is an effective first-line respiratory support for neonatal respiratory distress with a 77% success rate. Gestational age, antenatal steroids, disease severity scores, and oxygen requirements are significant predictors of outcome. Early identification of failure predictors enables timely intervention.